The meaning of Ontotheology in Heidegger’s Later Philosophy - Hani Ashrafi; Amir Maziar (پژوهشنامه فلسفه دین, 2018)
Martin Heidegger in his later writings and lectures shows that how metaphysics as ontotheology with the mere attention to beings and forgetting Being itself, considers beings’ whatness or essence on the one hand and their thatness or positioning in the causal chain and under the supreme being at the other hand. He believes that ontotheoligcal approach leads to the misunderstanding of Being, and as a result, pushing the divinity out of its proper position. In this article, we are going to investigate the meaning of ontotheology in the Heidegger’s later thinking and in order to do this, we pay special attention to his transition from an optimistic evaluation of fundamental metaphysics into a critical pessimistic one which specifies Heidegger’s later thinking. In this paper, via describing the ontotheological constitution of metaphysics from Heidegger’s view, it is shown that how oblivion of Being leads to the formation or born of metaphysical theology.